Multi-dimensional brand experiences in co-branded products across generations - Erlyana, Yana; Yi, Lim Jing (Institute of Advanced Engineering and Science, 2025)
As consumer expectations evolve, brands are tasked with creating multifaceted experiences that resonate with different generations. This study examines the influence of sensory, affective, behavioral, and cognitive brand experiences on consumer perceptions of co-branded products, with a focus on two key cohorts: Generation Y (Gen Y) and Generation Z (Gen Z). A mixed-methods approach, integrating quantitative surveys and qualitative focus groups, was employed to gain deeper insights into generational differences in brand engagement. The findings reveal that Gen Y consumers prioritize emotional and behavioral experiences, seeking meaningful interactions and emotional connections that align with their values and life stages. In contrast, Gen Z consumers are more interested in sensory novelty and cognitive engagement, favoring brands that emphasize originality, digital interactions, and distinctive experiences. Both generations showed strong reactions to behavioral factors, particularly direct product interactions. These insights highlight the importance of tailoring brand experience strategies to the unique preferences of each generation. By embedding sensory, emotional, and cognitive elements into brand experiences, companies can create deeper emotional connections with consumers, enhance brand value, and build long-term loyalty. The results offer actionable strategies for brand managers seeking differentiation and sustainable success in today’s competitive market environment.